Makueni Site, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
These are shots of farmers who were participating in listener groups of a radio show established by CCAFS and Mbaitu FM, and shared their experiences and practices. Photo: O. Thiong'o (CCAFS).